2013
DOI: 10.14260/jemds/1104
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Prescription Pattern of Non Steroidal Anti-Inflammatory Drugs in Medicine Out-Patient Clinic of a Rural Teaching Hospital

Abstract: Non Steroidal anti-inflammatory Drugs (NSAIDs) are most commonly prescribed drugs constituting more than 20% of all drug prescriptions. Prescription pattern study of NSAID was conducted in Medicine OPD of a rural teaching hospital with the objective of analyzing prescribing trend of NSAIDs, to evaluate co-prescription of Gastro-protective agents (GPAs) with NSAIDs and to determine number of prescribed NSAIDs falling within Drug utilization (DU) 90% segment. Overall 200 NSAID prescriptions were analysed. Preval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 18 publications
(19 reference statements)
1
4
0
Order By: Relevance
“…Consistent with results observed in earlier studies, the current study revealed that the most commonly prescribed NSAID was non-selective COX 1 inhibitors [9,10,18,19,20] i.e. A limitation of this study is that the sample was selected using a non-random sampling method, and this may have resulted in a biased sample as the intended population did not have equal sampling probability.…”
Section: Resultssupporting
confidence: 84%
“…Consistent with results observed in earlier studies, the current study revealed that the most commonly prescribed NSAID was non-selective COX 1 inhibitors [9,10,18,19,20] i.e. A limitation of this study is that the sample was selected using a non-random sampling method, and this may have resulted in a biased sample as the intended population did not have equal sampling probability.…”
Section: Resultssupporting
confidence: 84%
“…On evaluating the duration of therapy it was seen that 178 (48.1%) of the prescription the drug was prescribed up to 4-7 days. From other studies diclofenac sodium, meloxicam, paracetamol and ibuprofen were the commonly prescribed drugs, however dose was not mention on each of the study 2,3,4,13,16,17 it might be due to less side effects from the non-selective group or may be less knowledge over safety of COX-2 selective inhibitors over non-selective group.…”
Section: Discussionmentioning
confidence: 99%
“…In case of frequency of FDCs so prescribed in the study was found to be 28.37% which is much lower when comparing with the study conducted in Chitwan Medical College (49.61%) 6 , in case of other country combination of NSAID with other drug was more preferred than combination with paracetamol but on the contrary in this study such combination was the most common one rather than with other drugs. However other drugs like antihistaminic, skeletal muscle relaxant and serritopeptidase were also prescribed but as in co-prescribing form 4,10,17 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations